Rethinking the Ecological Crisis - Lee, Daryl (UnderCurrents: Journal of Critical Environmental Studies, 1991)
The stories we tell about nature reveal a great deal about how we think about ourselves, our society and the world in which we live. Nature is one of those potent cultural spaces within which a society plays out its dreams and fears, its ambitions and anxieties. As John Rodman reminds us, "just as our statements about other people tend also to be concealed statements about ourselves, so statements about nonhuman nature tend also to be concealed statements about the human condition. "1 Constructed through our various discourses, ideas of nature can be read as maps of our historically and culturally-constituted consciousness.